2012
DOI: 10.1007/s10652-012-9253-4
|View full text |Cite
|
Sign up to set email alerts
|

Dike-break induced flows: a simplified model

Abstract: A simplified model for the prediction of the steady-state outflow through a breach in an inland dike is presented. It consists in the application of the mass and momentum conservation principles to a macroscopic control volume. A proper definition of the shape of the control volume enables to take the main characteristics of the flow into account and thus to compensate for the extreme simplification of the spatial representation of the model. At the breach, a relation derived from the shallow-water equations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Similar behaviour was also identified by Stilmant et al (2013). It was observed that for smaller φ the differences in δ along the crest are less significant.…”
Section: Flow Over Weir Crestsupporting
confidence: 82%
“…Similar behaviour was also identified by Stilmant et al (2013). It was observed that for smaller φ the differences in δ along the crest are less significant.…”
Section: Flow Over Weir Crestsupporting
confidence: 82%